Penggunaan Kahoot! sebagai Alat Evaluasi untuk Meningkatkan Partisipasi Belajar Murid Kelas 8 SMPIT Insan Permata Malang: Penelitian - Muhammad Ilham Hidayatulloh; Agus Purnomo (Lembaga Penelitian dan Pengabdian Masyarakat, 2026)
This study aims to analyze the effectiveness of Kahoot! as an evaluation tool in increasing student participation and engagement in the learning process of Social Studies, specifically on the topic of Social Mobility, among eighth-grade students at SMPIT Insan Permata Malang. The background of this research is the low interest of students in Social Studies and the potential of Kahoot! as a gamification platform to create an enjoyable learning environment. The research method used is qualitative, with data collected through participatory observation, interviews, and document analysis. The results of this study are expected to provide a concrete picture of the improvement in students' learning interest, participation, and engagement following the implementation of Kahoot! in evaluations. Pedagogical implications and recommendations for teachers and educational institutions will also be discussed.